Исследование влияния доли Al2O3 в алюминатных люминофорах состава CaOxAl2O3, активированных Eu3+, на их люминесцентные свойства - Ботвина, Татьяна Михайловна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
In the present study, monophase phosphors based on aluminate matrix of CaO xAl-Os (where х=1,2,6), activated by EuS+(1-10 mol.%) were obtained. The maximum concentration of activator for each system was determined to improve the luminescent properties. It was shown that increase in aluminum oxide proportion is allow to incorporate more quantity of activator for creation of more active glow center that enhance the luminescent properties.